Nerve-Glial antigen 2: unmasking the enigmatic cellular identity in the central nervous system - Bottero, Marta; Pessina, Giada; Bason, Caterina; Vigo, Tiziana; Uccelli, Antonio; Ferrara, Giovanni (Frontiers in Immunology, 2024)
Chondroitin sulfate proteoglycans (CSPGs) are fundamental components of the extracellular matrix in the central nervous system (CNS). Among these, the Nerve-Glial antigen 2 (NG2) stands out as a transmembrane CSPG exclusively expressed in a different population of cells collectively termed NG2-expressing cells. These enigmatic cells, found throughout the developing and adult CNS, have been indicated with various names, including NG2 progenitor cells, polydendrocytes, synantocytes, NG2 cells, and NG2-Glia, but are more commonly referred to as oligodendrocyte progenitor cells.Characterized by high proliferation rates and unique morphology, NG2-expressing cells stand apart from neurons, astrocytes, and oligodendrocytes. Intriguingly, some NG2-expressing cells form functional glutamatergic synapses with neurons, challenging the long-held belief that only neurons possess the intricate machinery required for neurotransmission. In the CNS, the complexity surrounding NG2-expressing cells extends to their classification. Additionally, NG2 expression has been documented in pericytes and immune cells, suggesting a role in regulating brain innate immunity and neuro-immune crosstalk in homeostasis. Ongoing debates revolve around their heterogeneity, potential as progenitors for various cell types, responses to neuroinflammation, and the role of NG2. Therefore, this review aims to shed light on the enigma of NG2-expressing cells by delving into their structure, functions, and signaling pathways. We will critically evaluate the literature on NG2 expression across the CNS, and address the contentious issues surrounding their classification and roles in neuroinflammation and neurodegeneration. By unraveling the intricacies of NG2-expressing cells, we hope to pave the way for a more comprehensive understanding of their contributions to CNS health and during neurological disorders.